Do patient characteristics matter when calculating sample size for eczema clinical trials? - L. Howells; S. Gran; J. R. Chalmers; B. Stuart; M. Santer; L. Bradshaw; D. M. Gaunt; M. J. Ridd; L. A. A. Gerbens; P. I. Spuls; C. Huang; N. A. Francis; et al. (Wiley, 2021)
Abstract Background The Patient‐Oriented Eczema Measure (POEM) is the core outcome instrument recommended for measuring patient‐reported atopic eczema symptoms in clinical trials. To ensure that the statistical significance of clinical trial results is meaningful, trials are often designed by specifying the target difference in the primary outcome as part of the sample size calculation. One method used to specify the target difference is a score that corresponds to a standardized effect size. Objectives to assess how the standardized effect size of POEM scores vary across age, gender, ethnicity and disease severity. Methods This study combined data from five UK‐based randomized clinical trials of eczema treatments in order to assess differences in self‐reported eczema symptoms (POEM) corresponding to a standardized effect size (0.5 SD of baseline POEM scores) across age, gender, ethnicity and disease severity. Results POEM scores corresponding to 0.5 SD(baseline) were remarkably consistent across participants of varying ages, gender, ethnicity and disease severity from datasets of five UK trials in children (range 2.99-3.45). Conclusions This study provides information that can support those designing clinical trials to determine their sample size and can aid individuals interpreting trial results. Further exploration of differences in populations beyond the United Kingdom is needed.